The Contrapuntal Reading of Colonial Logic and the Play of Caricature in Ã¢â‚¬Å“Houseboy + MaidÃ¢â‚¬Â by Pramoedya Ananta Toer - Widiawati, Harfiyah; Harahap, Aris Masruri; Sihombing, Lambok Hermanto (Language Circle: Journal of Language and Literature, 2020)
Pramoedya Ananta ToerÃ¢â‚¬â„¢s works are highly distinguished for their strong realist characteristic and profound analysis of interactions among pre- and post- colonial human beings and their place in society. One of the works that portray such characteristics is Ã¢â‚¬Å“Houseboy + MaidÃ¢â‚¬Â, the first story in ToerÃ¢â‚¬â„¢s collection Tales from Djakarta: Caricatures of Circumstances and Their Human Beings. In this research, post-colonialism and contrapuntal reading proposed by Edward Said are used as methods to interpret a literary work whose narration is about two characters who live in post-colonial Indonesia, or rather post-revolutionary Indonesia. Their unfixed identities which are interrelated through the changing event of the plot indicates that their very destiny cannot be separated from the Ã¢â‚¬Å“politicality, sociality, and historicalityÃ¢â‚¬Â of much bigger entities.